2016
DOI: 10.4149/bll_2016_032
|View full text |Cite
|
Sign up to set email alerts
|

Significance of serum c-erbB-2 oncoprotein, insulin-like growth factor-1 and vascular endothelial growth factor levels in ovarian cancer

Abstract: OBJECTIVES: Our aim was to determine the predictive values of serum levels of several growth factors in ovarian cancer, including soluble c-erbB-2 oncoprotein, insulin-like growth factor-1 (IGF-1) and vascular endothelial growth factor (VEGF). BACKGROUND: Previous studies have shown that growth factors play an important role in carcinogenesis. METHODS: Two groups were established. One of them was the malignant group which included 41 patients with ovarian carcinoma and the other was the control group that was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Moreover, a previous study indicated that the expression of ErbB2 was positively correlated with the malignant potential of serous ovarian neoplasms [ 46 ]. However, there are also studies showing that serum VEGF levels might be used for diagnosis in ovarian cancer patients, while serum ErbB2 levels do not have a clinical significance in terms of ovarian cancer [ 47 ]. Interestingly, it has been reported that the level of VEGF in serum may depend on the expression of ErbB2 in patients with ovarian cancer [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a previous study indicated that the expression of ErbB2 was positively correlated with the malignant potential of serous ovarian neoplasms [ 46 ]. However, there are also studies showing that serum VEGF levels might be used for diagnosis in ovarian cancer patients, while serum ErbB2 levels do not have a clinical significance in terms of ovarian cancer [ 47 ]. Interestingly, it has been reported that the level of VEGF in serum may depend on the expression of ErbB2 in patients with ovarian cancer [ 48 ].…”
Section: Discussionmentioning
confidence: 99%